2016
DOI: 10.1002/ajhb.22927
|View full text |Cite
|
Sign up to set email alerts
|

Migration and nutritional status of Tarahumara schoolchildren from Chihuahua State (México)

Abstract: Migration reduces stunting and increases adiposity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 7 publications
1
2
0
Order By: Relevance
“…In previous research on schoolchildren performed by Balcázar, Pasquet, and De Garine (), increased obesogenic changes related to diet and physical activity patterns were observed in Tarahumara who migrated to urbanized places. Similar results of adiposity increases in urban places in Tarahumara children were observed by Benítez‐Hernández et al (). According to these observations, Monarrez‐Espino et al () referred to a higher prevalence of overweight Tarahumara children and female adolescents from urbanized areas (Monarrez‐Espino & Grainer, 2000).…”
Section: Discussionsupporting
confidence: 87%
“…In previous research on schoolchildren performed by Balcázar, Pasquet, and De Garine (), increased obesogenic changes related to diet and physical activity patterns were observed in Tarahumara who migrated to urbanized places. Similar results of adiposity increases in urban places in Tarahumara children were observed by Benítez‐Hernández et al (). According to these observations, Monarrez‐Espino et al () referred to a higher prevalence of overweight Tarahumara children and female adolescents from urbanized areas (Monarrez‐Espino & Grainer, 2000).…”
Section: Discussionsupporting
confidence: 87%
“…Studies from India, Mexico and Tanzania which explored the impact of migration on child growth in low-or middle-income countries, found that children born to internal (within-country) migrant mothers may have different nutritional outcomes than their non-migrant counterparts [21][22][23][24][25][26]. Notably, children of rural-urban migrant women tended to have a lower risk of undernutrition and a higher risk of overweight compared to the children of rural non-migrant women but the opposite when compared to children of urban nonmigrant women [21][22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…Studies from India, Mexico and Tanzania which explored the impact of migration on child growth in low-or middle-income countries, found that children born to internal (within-country) migrant mothers may have different nutritional outcomes than their non-migrant counterparts [21][22][23][24][25][26]. Notably, children of rural-urban migrant women tended to have a lower risk of undernutrition and a higher risk of overweight compared to the children of rural non-migrant women but the opposite when compared to children of urban nonmigrant women [21][22][23][24][25][26]. Research into the impact of internal migration on children found that children who migrated with their parents (as opposed to children born after maternal migration) had lower survival [27]; however, it is unclear if this pattern may also be the case for other health outcomes.…”
Section: Introductionmentioning
confidence: 99%